Assessment of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker on the split renal function in the patients with primary hypertension. Issue 20 (21st May 2021) - Zhang, Jingsi; Wang, Mingyu; Sun, Kehui; Ding, Yanchun
Abstract : Abstract: Bilateral kidney damage in hypertensive patients is not parallel. Angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (ACEI/ARB), as a commonly used antihypertensive drug, could protect kidney function and delay its deterioration. Most studies focused on overall renal function, but the researches on split renal function (SRF) are rare. We investigated the effects of ACEI/ARB on the SRF in patients with primary hypertension. Patients with primary hypertension (n = 429; male: 213; female: 216) admitted to our department between January 2014 and December 2016 were included in this study. The glomerular filtration rate (GFR) of split and total renal function were determined using diethylenetriaminepentaacetic acid tagged with 99mTc renal dynamic imaging method. For the same patient, the side with high GFR was considered as higher GFR kidney, whereas that with a low GFR was considered as lower GFR kidney. The split function score ( Q value) was utilized to evaluate the differences of bilateral renal function. The patients were divided into 3 groups based on the Q values (Group 1, Q value <5%; Group 2, Q value of 5%–10%; Group 3, Q value ≥10%). All the patients received antihypertensive therapy based on ACEI/ARB. The renal dynamic imaging was performed in the 1-year follow-up to investigate the changes of the SRF. Compared with the baseline level, significant decline was noticed in the serum creatinine (Scr) in Group 2 and Group 3 ( P < .05). The cystatin C in Group 3 showed significant decline ( P < .05). Compared with the baseline, there was significant decline in the Q value in Group 2, whereas the GFR of lower GFR kidney showed significant increase ( P < .05). No statistical differences were noticed in the Q value and split GFR in Group 1 and Group 3 ( P > .05). In primary hypertension patients, ACEI/ARB therapy could improve the SRF of lower GFR kidney in the presence of certain differences between the SRF. As a result, the SRF difference was reduced. In case of Q value in a range of 5% to 10%, ACEI/ARB could improve the renal function effectively. It may be significant for the design of antihypertensive drugs.